Analisis Perputaran Piutang Dan Perputaran Modal Kerja Dalam Menilai Profitabilitas Pada PT Selamat Sempurna Tbk Yang Terdaftar Di BEI - Dahlia Putri Indah Sari (STIE Jambatan Bulan, 2022)
Kata Kunci: Accounts Receivable Turnover, Working Capital Turnover, Profitability This study aims to determine how accounts receivable turnover and working capital turnover in assessing profitability. The research object is PT. Selamat Sempurna Tbk taken from financial statements for 5 years in the period 2016 - 2020. This study uses a qualitative descriptive method consisting of three variables, namely receivables turnover and capital turnover as the independent variable and profitability as the dependent variable using the calculation of return on assets. The data analysis method used in this research is the analysis of receivables turnover, capital turnover and profitability which are measured using the calculation of return on assets. The calculation results show that the average receivables turnover for the 5-year period 2016 - 2020 is 3.96 times per year. Overall, it is categorized as quite good, when viewed from general standards or the industry average, which is 7.2 times. The average working capital turnover for 5 years in the 2016 - 2020 period of 2.56 times per year is overall categorized as poor, when viewed from the industry standard average, which is above 6 times. for the average return on assets for the 5-year period 2016 - 2020 of 21.02%, overall it is categorized as very good, when viewed from the industry standard, which is 5.98%. then according to the calculation that receivables turnover and working capital turnover can assess profitability as measured using return on assets for the 5-year period from 2016 to 2020, the result is a contribution of 13.48% and the rest is influenced by other factors not examined in this study.